Lockdown : escape from Furnace / 1. - Smith, Alexander Gordon, 1979- (Escape from Furnace, 2009)
When fourteen-year-old Alex is framed for murder, he becomes an inmate in the Furnace Penitentiary, where brutal inmates and sadistic guards reign, boys who disappear in the middle of the night sometimes return weirdly altered, and escape might just be possible.